Optimization of the ratio of aniline, ammonium persulfate, para-toluenesulfonic acid for the synthesis of conducting polyaniline and its use in energy storage devices - Das, Tapas; Pandey, Vikas Kumar; Verma, Sanjeev; Pandey, Saurabh Kumar; Verma, Bhawna (John Wiley and Sons Ltd, 2022)
We have successfully synthesized para-toluenesulfonic acid (PTSA)-based conducting polyaniline (PA) by using ammonium persulfate (APS) as oxidant for supercapacitor electrode applications. The primary aim is to find out the optimized ratio of APS:aniline and aniline:PTSA based on the electrochemical performances of the fabricated electrodes. PA having APS:aniline ratio of 1.25:1 and aniline:PTSA ratio of 2:1 exhibited the highest value of specific capacitance, specific energy, specific power, and coulombic efficiency of 82.22 F/g, 11.42 Wh/kg, 124.99 W/kg, and 95.95%, respectively. It offers very low charge transfer resistance of 3.1 Ω during the electrochemical processes. The cycle life of the corresponding system is the largest among all, which is 88.97% retention after 2000 cycles. The robust electrochemical behavior may be due to the uniform rod-shaped morphology of the corresponding system, which may be providing seamless movement of the electrolyte ions to the electrochemical active sites along with proper electrical connection.
This paper is submitted by the author of IIT (BHU), Varanasi
Keywords: coulombic efficiency; para-toluenesulfonic acid; polyaniline; specific power; supercapacitor